The Effect of Communication Technology Development on the Intelligence of Children through Educational Value System Management - Ade Tutty R. Rosa (International Journal of Emerging Issues in Early Childhood Education, 2019)
The development of IT in the digital era 4.0 currently provides a considerable and different influence on each user, including children. In general, the problems in the world of education include the quality and quantity of education related to quality and equality in obtaining access to education without any gaps and exceptions. The solution that can be developed is the optimization of the role of Information and Communication Technology (ICT) in the world of education. One of the roles of ICT in education is realized by the development of online learning (e-learning) or the direct use of ICTs for children. Many changes - changes in different new values can have a positive impact on children's growth, especially on intellectual intelligence, intelligence emotional, spiritual, and social intelligence. ICTs have a good influence on children's intellectual, emotional, spiritual and social intelligence; IT brings a bad influence on children's intellectual intelligence; IT has a pretty good influence on children's emotional intelligence; IT has a pretty good influence on children's spiritual intelligence, IT has a good influence on children's social intelligence. Importance of Parents has a role to be able to know the changes that occur during child development.